Implementasi Media Permainan Tingkatkan Motivasi dan Hasil Belajar IPAS Peserta Didik Kelas III - Rury Aisyaturida; Marista Dwi Rahmayantis; Ria Wahyuning Budiasri (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study aims to evaluate the use of educational games as a learning medium to enhance students' motivation and improve the quality of Natural and Social Sciences (IPAS) instruction at the elementary school level. The research employed a classroom action research approach consisting of two cycles. Data were collected through observations, documentation, assessment rubrics, tests, and field notes. The games used in the study included "whisper chain" and "thread pull," both of which were adapted to suit the IPAS subject matter. These games were not intended to introduce new concepts but rather to develop students' skills. The results showed that the games successfully stimulated students’ enthusiasm and encouraged them to engage in enjoyable learning activities. The findings indicate that using games as a learning medium is effective in enhancing the quality of IPAS instruction in elementary schools. The study concludes that: 1) Games are implemented after the teacher delivers the material to reinforce students' understanding; 2) Educational games have proven to be beneficial in improving the quality of IPAS learning at the elementary level.